Analisis Kadar Kalsium (Ca) Pada Lansia Di Panti Perlindungan Dan Rehabilitasi Sosial Lanjut Usia Provinsi Kalimantan Selatan: Analysis of Calsium (Ca) Levels In The Elderly At The “Budi Sejahtera” Social Shalter and Rehabilitation Home For The Elderly in Sout Kalimantan - Amalia, Nurul; Arsyad, Muhammad; Khafifah, Khafifah (Borneo Journal of Medical Laboratory Technology, 2024)
The elderly, or senior citizens, are a group of individuals who have reached old age. People in this age group are usually more susceptible to health problems. Calcium is a nutrient that is essential for the body and is the most abundant mineral found in the body, accounting for approximately 1.5-2% of an adult's body weight or about 1kg. Insufficient or excessive calcium intake can lead to abnormal metabolism. Calcium deficiency can result in osteoporosis and hypocalcemia, while excess calcium can cause hypercalcemia. The purpose of this study is to determine the calcium (Ca) levels in the elderly at the "Budi Sejahtera" Social Protection and Rehabilitation Home for the Elderly in South Kalimantan Province. The research design used in this study is a descriptive survey, which is a method used to describe or analyze research findings but not to draw broader conclusions. The calcium levels in the elderly were measured using a cross-sectional design, which observes population or sample data only once at the same time. The sampling was conducted on June 10, 2023. The sample used was blood from the elderly at the "Budi Sejahtera" Social Protection and Rehabilitation Home for the Elderly in South Kalimantan Province, with purposive sampling technique, which is a sampling technique based on specific criteria, resulting in 30 participants out of 69. The calcium levels (Ca) of the 30 respondents were calculated to have a mean of 6.81mg/dl, a maximum of 10.80 mg/dl, and a minimum of 3.30 mg/dl. The results showed that 21 respondents had low calcium levels, 8 respondents had normal levels, and 1 respondent had high calcium levels. Based on the characteristics of the 30 respondents, there were 18 male and female respondents in the younger age group (60-74 years), and 3 respondents in the older age group (75-95 year).